Remnant cholesterol predicts risk of recurrent thrombosis beyond LDL-cholesterol in patients with antiphospholipid syndrome - Cai, Bin; Zhou, Yangzhong; Yang, Xinzhuang; Wang, Zhaoqing; Huang, Can; Xiao, Qingqing; Jiang, Hui; Zhao, Yuan; Tian, Xinping; Wang, Qian; Li, Guanqiao; Li, Mengtao; et al. (BMC medicine, 2025)
Antiphospholipid syndrome (APS) is notably linked to thrombotic events, particularly cardiovascular disease (CVD). The role of remnant cholesterol (RC) in predicting CVD risk is established, yet its relationship with thrombotic risk in APS patients remains to be elucidated. This study aims to assess the association between RC and recurrent thrombotic risk in patients with APS. A prospective analysis was conducted based on a cohort of APS patients who met the 2006 Sydney revised classification criteria. Thrombotic risks associated with varying levels of RC were evaluated using Kaplan-Meier survival analysis and Cox proportional hazards regression models. Mendelian randomization (MR) was applied to examine the causal link between RC and different types of thrombotic events. A total of 325 patients with APS were enrolled in this study. Over a median follow-up of 35 months, 51 patients experienced thrombotic events, including 24 venous, 19 arterial, and 16 microvascular incidents. Patients with RC levels above 0.60 mmol/L exhibited significantly higher risks, with multivariable-adjusted hazard ratio (and 95% confidence interval) for all-cause, venous, arterial thrombosis, and microvascular disease being 5.05 (2.23-11.41), 6.34 (1.71-23.54), 3.79 (1.00-14.32), and 4.36 (1.08-17.58), respectively. Notably, elevated RC remained a significant thrombotic risk factor even in patients with normal conventional lipid profiles. MR analysis revealed a significant causal association between RC and arterial thrombosis, but not venous thrombosis. Elevated RC is linked to a substantial increase in the risk of thrombotic events in APS patients. These findings suggest that RC could be a valuable marker for thrombotic risk in this population and a potential target for therapeutic intervention.